2007
DOI: 10.1086/519847
|View full text |Cite
|
Sign up to set email alerts
|

Infant Morbidity, Mortality, and Breast Milk Immunologic Profiles among Breast‐Feeding HIV‐Infected and HIV‐Uninfected Women in Botswana

Abstract: (ClinicalTrials.Gov) identifiers: NCT00197691 and NCT00197652.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
137
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 23 publications
11
137
2
Order By: Relevance
“…The risk of all-cause hospital admissions in the first 18 months of life was significantly higher in HEU children compared with HIV-unexposed children, which is consistent with the findings of previous studies conducted in the context of available antiretrovirals for PMTCT [7,9,32]. Diarrhea (loose or watery stools more than three times in 1 day according to ICD-10 coding system) was more frequent among HEU compared with HIV-unexposed children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The risk of all-cause hospital admissions in the first 18 months of life was significantly higher in HEU children compared with HIV-unexposed children, which is consistent with the findings of previous studies conducted in the context of available antiretrovirals for PMTCT [7,9,32]. Diarrhea (loose or watery stools more than three times in 1 day according to ICD-10 coding system) was more frequent among HEU compared with HIV-unexposed children.…”
Section: Discussionsupporting
confidence: 89%
“…Cohort studies from other sub-Saharan countries have shown that, before the availability of ART, HEU children had a higher mortality risk than HIV-unexposed children [4,6,29]. However, reports on mortality in HEU and HIVunexposed children in the ARTera are scarce, and results are heterogeneous [19,[30][31][32][33]. Mortality rate in HEU children in this study (2.2 deaths per 100 live births per year at risk) was lower than that reported from other countries in sub-Saharan Africa in the ART era, though Cox proportional hazard models.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similarly, several studies have reported increased mortality rates in HEU infants, whereas others have not found this association. 7,[11][12][13][14] Factors shown to be predictive of mortality in HEU children include malnutrition, clinically diagnosed Pneumocystis jirovecii pneumonia or very severe pneumonia, severe anemia, not breastfeeding, and advanced maternal HIV. 7,10,15,16 The recent expansion of access to strategies for the prevention of mother to child transmission of HIV (PMTCT) has led to marked reductions in HIV acquisition among children born to HIV-infected women, including in South Africa (2.7% in 2011) 17 ; however, the prevalence of HIV among pregnant women and consequently in utero HIV exposure of fetuses, has remained unchanged (30% in 2011).…”
mentioning
confidence: 99%
“…Breast milk is known to contain many chemokines and cytokines (24,41), some of which may influence HIV-1 infection and transmission (7,12,20). Epidemiologic studies have sought to find correlations between individual breast milk components and transmission of HIV-1 through breast-feeding or between HIV-infected and noninfected women (8,35,42,44). However, a clear relationship has not been established, making it likely that multiple components interact to affect cell activation and virus replication within the breast milk milieu.…”
Section: Discussionmentioning
confidence: 99%